2019
DOI: 10.1136/archdischild-2019-316871
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of automated insulin delivery guided by continuous glucose monitoring in preterm infants

Abstract: ObjectiveClosed-loop systems have been used to optimise insulin delivery in children with diabetes, but they have not been tested in neonatal intensive care. Extremely preterm infants are prone to hyperglycaemia and hypoglycaemia; both of which have been associated with adverse outcomes. Insulin sensitivity is notoriously variable in these babies and glucose control is time-consuming, with management requiring frequent changes of dextrose-containing fluids and careful monitoring of insulin treatment. We aimed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…While off-label use of medication is both common practice and a necessity in newborn infants, there are few examples of off-label uses of medical devices, rtCGM being a notable exception [ 7 , 8 , 19 - 24 ]. CBG tests are the current standard of care in the management of neonatal hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While off-label use of medication is both common practice and a necessity in newborn infants, there are few examples of off-label uses of medical devices, rtCGM being a notable exception [ 7 , 8 , 19 - 24 ]. CBG tests are the current standard of care in the management of neonatal hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on rtCGM use for glycemic management in neonates is limited, and there is no evidence of calibration-free rtCGM systems in infants so far. Benefits with respect to glycemic control [ 7 ] and less procedural pain [ 8 ] have been previously described for very low-birth-weight preterm infants in a feasibility study. Furthermore, a study found continuous tissue glucose monitoring to be helpful to identify infants at risk for metabolic instabilities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, remote monitoring with Dexcom G6 was evaluated using Dexcom Follow app in Reutrakul et al 4 for noncritical patients with coronavirus disease 2019 (COVID-19). Other relevant telemetry studies worth to mention that controlled multiple patients without COVID-19 are Beardsall et al 5 and Singh et al 6 This letter illustrates the potential of a new platform for simultaneous remote monitoring of multiple intensive care unit (ICU) and/or quarantined patients. To our best knowledge, this is the first multicenter, multisensor, multipatient, and potentially multitherapy platform for remote glucose monitoring employed in critically ill COVID patients.…”
mentioning
confidence: 91%
“…4 Hospital Italiano de Buenos Aires, Buenos Aires, Argentina. 5 Hospital de Pediatría J. P. Garrahan, Buenos Aires, Argentina. Garrahan.…”
unclassified
“…The development of real-time CGM, which provides continuous glucose data and identifies early trends in glucose concentrations can inform clinical decisions, and has been successfully used in adult 11 and paediatric intensive care. 12 , 13 , 14 Preliminary data suggest it is feasible in preterm infants 10 , 15 , 16 , 17 and could allow earlier detection and potentially prevention of exposure to extreme glucose concentrations. 17 , 18 We aimed to formally evaluate the use of real-time CGM to guide the clinical management of glycaemic control and use of insulin in preterm infants.…”
Section: Introductionmentioning
confidence: 99%